Time for the Two-spirits: Shaping the inclusive policy environment for Hispanics and Transgenders through Global Health Diplomacy - Chattu, Vijay Kumar; Mario, O Laplume; Soosanna, Kumary (Wolters Kluwer, 2018)
Minority populations in the world are permanently challenged with unequal living and working conditions in their daily lives that compromise their access to needed clinical and preventive services. When we discuss the healthcare conditions for minorities we must address the social determinants of access that are ultimately determined by the policies and politics of the governments. Renowned experts of Quality in Health care have been critical of the current design and implementation of randomized clinical trials, the gold standard of clinical research, because they believe that they often, but not always, presume a linear, mechanistic system when in fact improvement in Health care takes place within complex adaptive systems that evolve. The combined action of ignorance and prejudice can impair the efficient recruitment and retaining of “different people” like Hispanics and Transgender that have long suffered discrimination in their access to health care services in spite that they are more prone to have chronic conditions. Even though the incidence of AIDS has decreased in the general population during the past two decades, it is continuing in the gay population due to educational issues, discrimination in health care access and lack of proper public and private funding for the life-saving retroviral medication. The declaration of the “International Conference on Health Promotion” sponsored by PAHO in Colombia in 1992 have emphasized the aim of reducing differences in health status as well as ensuring equal opportunities and resources to enable all people to achieve their full health potential. Through the entreaties of the Global Health Diplomacy, the resiliently hard core issues of discrimination and marginalization must be addressed by encouraging public policies that guarantee equity and ensure access for the most socially castigated groups.